بناء موضوع الارهاب من طرف خبرة مراكز الفكر في الولايات المتحدة الأمريكية والشرق الأوسط منذ 11 سبتمبر 2001 - منير ليمان (University of M'Sila, 2024)
تتناول هذه الأطروحة كيفية بناء الارهاب كموضوع للخبرة من طرف مراكز التفكير الأمريكية و الشرق أوسطية بعد 11 سبتمبر 2001. انطلاقا من اعتبار أن الخبراء ينتجون براديغمات عمل وليس نماذج فهم نظرية، فإن طبيعة الخبرة المنتجة عن الارهاب تتميز بنزعتها نحو تحييد التفسيرات الموضوعية والعقلانية له، وهو ما يجعل منها خبرة مسيسة قبل كل شيء. تقترح النماذج الخبيرة المهيمنة فهما هوياتيا للإرهاب، فهي تبحث عن الربط بين الفعل الارهابي وهوية العدو يهدف تحديد الحرب التي ينبغي على السياسيين والعسكريين القيام بها. يهيمن هذا التصور على المستوى العابر للأوطان أيضا، فهو ينتقل من المركز الأمريكي نحو المحيط الشرق أوسطي ليصنع إجماعا للخبراء. بالاستناد على مفهوم تشويه التفضيلات لتيمور كوران، قدمنا شرحا لآلية تشكل الإجماع بين الخبراء، و فسرناه أيضا بهيمنة فاعلين آخرين من الحقلين السياسي والعسكري-الاستخباراتي على الخبراء
The present thesis aims to analyze how the concept of terrorism has been constructed by the expertise of think tanks (TT) in the United States and the Middle East since September 11, 2001. Giventhat experts are charged withgenerating action-oriented paradigms rather than theoretical explanations, expertise on terrorism is marked by its tendency to neutralize objective and rational explanations, making it primarily a politicized knowledge. The dominant expert paradigms conceptualize terrorism as identity-based; they consist of establishing the link between the terrorist act and the figure of the enemy with the aim of determining the war that political and military actors must conduct. This conceptualization of terrorism is dominant on a transnational level; it shifts from the U.S. center to the Middle Eastern periphery and serves to shape expert consensus. Using the concept of preference falsification developed by TimurKuran, experts tend to select the explanations they express publicly, which necessarily differ from their private preferences. If certain expert explanations are widely shared in the political debate, this means that experts are dominated by the conceptions particularly produced by other political and military fields.
Keywords: الخبرة، مراكز التفكير، الارهاب، الولايات المتحدة الأمريكية، الشرق الأوسط.; Expertise; Think Tanks; Terrorism; United States; Middle East.